Exercise testing and risk assessment of pulmonary hypertension - Alharbi, Samar A.; Shaeri, Intisar A.; Alharith, Salem S.; Almutairi, Shatha S.; Aljaafari, Ahmed N.; Alshahrani, Nouf F.; Alalhareth, Naif H.; Alshahrani, Saad A.; Alsomali, Abdullah J.; Aldhaeefi, Maram Y.; Hakami, Ghaym M. (International Journal Of Community Medicine And Public Health, 2023)
Managing pulmonary hypertension (PH) involves approaches to relieve symptoms, slow disease progression, and improve patient outcomes. Advances in treatment strategies, risk assessment methods, and lifestyle adjustments have significantly improved PH care. While PH has no cure, treatment options are available to alleviate symptoms, extend life expectancy, and slow disease advancement. Tailoring treatment strategies based on the type and severity of PH as individual patient response and tolerance is crucial. The main goals include alleviating symptoms, enhancing quality of life, improving capacity, and increasing survival rates. Diagnosis and management require evaluation and regular follow-up due to the complexity of PH treatments. Different medical approaches play a role in symptom relief. Improving overall system function. Oxygen therapy and procedures such as septostomy or lung transplantation may be warranted, contingent on disease severity. Lifestyle modifications, encompassing exercise training, smoking cessation, and weight management, complement pharmacological interventions. Risk assessment tools, typified by the REVEAL risk score, have revolutionized PH care by facilitating personalized therapeutic approaches. Genetic factors are increasingly considered, heralding a new era in tailored treatment. While challenges persist, ongoing research endeavors promise.